(Re-defining) the trust of the specifically enforceable contract of sale—the vendor purchaser constructive trust. Issue 3 (24th January 2018) - Meagher, Jacob J
Abstract: This article provides a comprehensive outline and consequential redefinition of the oldest form of constructive trust occurring in English law, 1 the vendor–purchaser constructive trust (VPCT). This species of constructive trust arises by operation of law, once primarily in the context of sales of land, but now in the context of any specifically enforceable contract of sale (eg shares in a private company). 2 The VPCT primarily protects the interest and equities each party to the contract has in its performance, 3 and exists only as an equitable consequence of the contract, embodying both proprietary interests and a mutuality of obligations between vendor and purchaser, constructive trustee and beneficiary. This trust springs from Equity's ( an attempt has been made to use Equity in capital when emphasising the Chancery jurisdiction in contrast to its Common Law counterpart, otherwise lowercase equity indicates its usage in practice, ie a mere equity ) doctrinal foundations, and so far, suffers from a paucity of generalized analysis. This article clarifies, and identifies the key elements of the VPCT, rejecting the current orthodoxy, and restating the trusts' principle by isolating Equity's techniques; contract formation, through to equitable-conversion of title, equitable interests, lien, enforcement, to final conveyance, until this doctrine is manifestly unambiguous.